1.(1)原式=-10a³b³c (2)原式=1/2abx⁴ (3)原式=12×1010 (4)原式=-3x⁶
2.(1)原式=m²n²·(-m²n)=-m⁴n³
(2)原式=8m³.1/16m²=2m5
(3)原式=x²y³-8x²y³=-7x²y³.
(4)原式=2m⁴n³+10m⁴n³=12m⁴n³
3.4.6吨
4.(1)原式=-3y²+6y (2)原式=-12x³+4x²-3x (3)原式=-2x²y+5xy²+xy (4)原式=4y²-21y+5 (5)原式=8x²+14x+3 (6)原式=1/2x²-19/12x-3
5.(1)原式=10x²+20x+x²-x=11x²+19x
(2)原式=2a³+6a²-4a-2a³-4a²+2a-2=2a²-2a-2
6.(1)原式=ab-ac-bc+ab+ac-bc=2ab-2bc
当a=1/2,b=-1,c=-2时,原式=2×1/2×(-1)-2×(-1)×(-2)=-5
(2)原式=x²-2xy-xy+2y²-(3x²-9xy-2xy+6y²)=x²-2xy-xy+2y²-3x²+9xy+2xy-6y²=-2x²+8xy-4y².
当x=4,y=-1时,原式=-2×4²+8×4×(-1)-4×(-1)²=-68.
7.(1)去括号,得x²-5x+6+18=x²+10x+9,移项、合并同类项,得-15x=-15,系数化为1,得x=1。
(2)去括号,得x³+x²+x-6x²-6x-6-x³+x=2x-5x²,移项、合并同类项,得-6x=6,系数化为1,得x=-1。
8.